Influence of the cultivation medium and pH on the pigmentation of Trichophyton rubrum - Blechert, Oliver; Zheng, Hailin; Zang, Xiaohui; Wang, Qiong; Liu, Weida (PLOS ONE, 2019)
Trichophyton rubrum is a human pathogenic fungus. As a dermatophyte it causes athlete's foot, fungal infection of nails, jock itch and ringworm. The pigmentation of T. rubrum is variable and can range from white or yellow to wine-red. We demonstrate that the pigmentation is strongly influenced by pH. Under alkaline conditions, T. rubrum has a red pigmentation, whereas at acid conditions, T. rubrum has a yellow pigmentation. Moreover, the color change immediately from yellow to red by adding NaOH and reverse immediately from red to yellow by adding HCl. We suggest that the chemical compound Xanthomegnin is responsible for red as well for yellow pigmentation in T. rubrum. To figure out, why T. rubrum has red pigmentation on Trichophyton medium, adjust to alkaline, but not on Synthetic-Complete medium, also adjusted to alkaline, we measure the pH of liquid media, adjusted to pH 3.5, 6 and 8, over a period of four weeks. The pH of both cultivation media changes significantly, with a maximum of five pH levels. Whereas the Trichophyton medium, initially adjusted to pH 8, stays alkaline, the pH of the Synthetic-Complete medium drops to acid conditions. The acidification of the SC medium and the alkalization of the Trichophyton medium explains the different pigment color of the T. rubrum colonies.